Kælvningsfeber. Foredrag i det kgl. Landhusholdningsselskab d. 30te Januar 1884. - Oppermann, L. V. (Tidsskrift for Landøkonomi, 2018)
Kælvningsfeber. Foredrag i det kgl. Landhusholdningsselskab d. 30te Januar 1884.